Diseño y construcción de un prototipo para capturar señales bioeléctricas musculares del antebrazo, utilizando un procesador ARM - Maza Guarnizo, Darwin José (2016)
This titling project aims to create a device that allows sensing and processing bioelectric signals from the forearm muscle contractions. To achieve an interaction between a desktop or mobile application. As a first instance several branches of study such as medicine, electronics and computers, using free tools both software and hardware to build a bracelet able to capture and process biosignals merge. For the stage of signal processing techniques, algorithms and different classifiers (neural networks, machine vector) used to achieve pattern recognition is described. The next step is to create an application for a mobile device with Android system, which allows the configuration of the actions of the forearm versus later commands allow interaction between prototype and a desktop application. Finally the interaction between the developed and the developed prototype applications will be shown, reaching prove that uniting various branches of study can build devices with advanced technology and low cost, able to get signals on different muscle groups that allow interaction man machine.